Spain : Report on the Observance of Standards and Codes: Summary Assessments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents assessment results for the current state of the implementation of the Basel Core Principles for Effective Banking Supervision (BCP) in Spain. It found that significant changes have occurred in Spain since the last Financial Sector Assessment Program. The most serious has been the deterioration of the economy and the real estate sector. The core supervisory process at the Banco de Espana (BdE) is strong and is supported by qualified staff and an experienced cadre of inspectors, but there are areas of concern.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet